Employee Assistance Program as the Supporting System of Quality of Work Life to Cope with Occupational Stress - L. Verina Halim Secapramana; Satryo Anggoro; V. Heru Hariyanto (Journal of Educational, Health and Community Psychology, 2020)
Increasing productivity has always been an important issue in the context of management. Â Efforts in this direction are often demands that cause occupational stress, so that a counterproductive situation may occur. Quality of Work Life (QWL) is one of the hot issues that arise to neutralize stressful conditions by creating a more comfortable and more humane working climate. The Employee Assistance Program (EAP) as an intervention can be expected to function as a supporting system. The assessment was conducted for 67 employees. The questionnaire, interview, FGD, and SWOT analysis methods are used in all three stages, the pre-assessment stage, the assessment stage, and the intervention stage. From the Occupational Inventory Stress-Revised (Osipow, 1998), there are four most significant stressor areas and personal resources that are underutilized in managing stressors. The intervention program is directed at curative and preventive services through the EAP design.